Terminal Ballistics - Rosenberg, Zvi.; Dekel, Erez.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book comprehensively discusses essential aspects of terminal ballistics, combining experimental data, numerical simulations and analytical modeling. Employing a unique approach to numerical simulations as a measure of sensitivity for the major physical parameters, the new edition also includes the following features: new figures to better illustrate the problems discussed; improved explanations for the equation of state of a solid and for the cavity expansion process; new data concerning the Kolsky bar test; and a discussion of analytical modeling for the hole diameter in a thin metallic plate impacted by a shaped charge jet. The section on thick concrete targets penetrated by rigid projectiles has now been expanded to include the latest findings, and two new sections have been added: one on a novel approach to the perforation of thin concrete slabs, and one on testing the failure of thin metallic plates using a hydrodynamic ram.
Experimental Techniques -- Material Models for Numerical Simulations.-Rigid Penetrators -- Plate Perforation -- Eroding Penetrators -- Defeat by High Strength Targets -- Asymmetric Interactions.
Keywords: Engineering design; Building materials; Mechanics, Applied; Solids; Metals; Engineering Design; Structural Materials; Solid Mechanics; Metals and Alloys